Analisis Kegiatan Bongkar Muat KM. X di Daerah 3T (Tertinggal, Terdepan, dan Terluar) - Julviakmal Ilham Firmanda; Firdaus Sitepu; Ardhiana Puspitacandri; Samsul Huda (Pusat riset dan Inovasi Nasional, 2025)
Loading and unloading is the activity of moving goods from land transportation, and to carry out the activity of moving the load, adequate facilities or equipment are needed in a shipping method or procedure. The implementation of loading and unloading occurs various obstacles that often slow down loading and unloading activities, especially in the 3T (Underdeveloped, Frontier, and Outermost) areas. The equipment and facilities available by the port greatly affect how fast or slow the loading and unloading activities take place. This study aims to determine: 1) What are the factors that cause delays in the loading and unloading process of containers in the 3T area 2) What efforts are made by company and port management in overcoming delays in the loading and unloading process of containers in the 3T area. The method used by the researcher this time is descriptive qualitative. Primary data in this study were obtained directly through interviews, observations (observations) and also documentation. The main factors that are the main causes of why loading and unloading activities in the 3T area are ineffective and inefficient, namely the lack of adequate loading and unloading equipment and port facilities, the lack of human resources and skills from TKBM, as well as geographical conditions and bad weather. This situation causes loading and unloading activities to be ineffective.